An Examination of The Belief in ’Ikhtilaj (Palpitation) Among Yoruba Muslims Within the Context of Wahy (Divine Revelation) And Tatayyur (Pessimism) - Shaykh Luqman Jimoh; Luqman Zakariyah (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
Abstract The Yoruba people are majorly found in the South-Western part of Nigeria. While they were traditionally idol worshippers, Islam and Christianity have with time gained firm root among them. As traditional people, they believe in omen, premonition and intuition. In addition to these beliefs, the Muslims among them equally express belief in ’ikhtilaj which technically is palpitation of any part of the body because of which one fills pulses in that part. The pulse is experienced repeatedly in the affected part which may be the neck, eyes, lips, thighs etc. The belief among some Yoruba Muslims is that ’ikhtilaj is a form of wahywhile it is considered by some others as a form of tatayyur. This study therefore examined the belief in ’ikhtilaj among Yoruba Muslims with the view to determining whether it has interpretative meaning and whether it is to be considered as belonging to the class of tatayyur or wahy. To achieve the objectives of the study, the doctrinal exegetical analytical methods were adopted to analyze textual authorities from Islamic texts scholarly works and historical documents, also qualitative approach was employed through semi structural interviews. Findings, however, revealed that there are two opposing views among Yoruba Muslims on whether ’ikhtilaj has interpretative meaning and whether it is to be considered as belonging to the class of tatayyur or wahy. The study concluded that in the light of Islamic law principles, ’ikhtilaj has no interpretative meaning and it is to be considered as tatayyurand notwahy.